The Role of Historical Streets and Mixed-Era Buildings in Shaping Urban Identity and Quality: A Case Study of Zhongshan North-South Road, Taipei City - Lan, Chih-Wen (MAJ - Malaysia Architectural Journal, 2025)
Streets are essential to urban transportation and are key to shaping a city's identity and quality. In large urban settings, unique features are often captured in streets that blend historical and contemporary elements. However, modern urban planning frequently emphasizes the quantity of public facilities over the quality of urban life, potentially overlooking the importance of urban identity. This research argues that mixed-era buildings and historical streets, such as Zhongshan North-South Road in Taipei City, should be seen not as obstacles to development but as vital elements that enhance urban identity and quality. Zhongshan North-South Road, which has evolved through significant historical periods, including the Japanese colonial era and the Cold War, serves as a case study to demonstrate the influence of historical streets on urban vitality. The study underscores the importance of urban regeneration that values historical elements, providing insights into how mixed-era locations contribute to a unique urban environment value and serve as a reference for historical urban preservation.